2017
DOI: 10.1016/j.kint.2016.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Acid retention with reduced glomerular filtration rate increases urine biomarkers of kidney and bone injury

Abstract: Diets high in acid of developed societies that do not cause metabolic acidosis in patients with chronic kidney disease nevertheless appear to cause acid retention with associated morbidity, particularly in those with reduced glomerular filtration rate. Here we used a rat 2/3 nephrectomy model of chronic kidney disease to study induction and maintenance of acid retention and its consequences on indicators of kidney and bone injury. Dietary acid was increased in animals eating base-producing soy protein with aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 36 publications
3
40
0
Order By: Relevance
“…| TRC101 significantly increased mean serum bicarbonate (SBC) throughout the 2-week treatment period, with serum bicarbonate returning to baseline after treatment discontinuation. Mean SBC response with treatment over the 14-day intervention period (days [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and during the 7-to 14-day off-treatment follow-up period (days 15-28) by dose group. Treatment with TRC101 caused a steady increase in mean SBC in all TRC101 dose groups during the on-treatment period.…”
Section: Total N=135mentioning
confidence: 99%
See 1 more Smart Citation
“…| TRC101 significantly increased mean serum bicarbonate (SBC) throughout the 2-week treatment period, with serum bicarbonate returning to baseline after treatment discontinuation. Mean SBC response with treatment over the 14-day intervention period (days [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and during the 7-to 14-day off-treatment follow-up period (days 15-28) by dose group. Treatment with TRC101 caused a steady increase in mean SBC in all TRC101 dose groups during the on-treatment period.…”
Section: Total N=135mentioning
confidence: 99%
“…Metabolic acidosis associated with CKD is characterized by an imbalance in acid production relative to excretion, resulting in the depletion of the extracellular buffer, bicarbonate, as well as buffers mobilized from bone and muscle (1)(2)(3)(4)(5)(6). Chronic metabolic acidosis is common in advanced stages of CKD, and it is associated with adverse consequences, including increased mortality, acceleration of kidney disease progression, increased muscle breakdown and insulin resistance, and the development or exacerbation of bone disease (5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Wesson et al 13 reported recently that incremental increases in dietary acid loads in rats after 2/3 nephrectomy (model of progressive CKD) displayed evidence of cortical interstitial acid retention (compared with sham-operated controls). The renal cortical acid milieu in these animals was associated with higher excretion rates of N-acetyl-b-Dglucosaminidase, consistent with the development of tubulointerstitial disease.…”
mentioning
confidence: 99%
“…Correction of acidosis, as well as maintenance of regular physical activity and correction of obesity are two further fundamental issues; a plant-based approach may be of help, in particular for acidosis correction [44,45,46,47,48]. All these issues merge into the need for higher food-awareness, a comprehensive concept that needs to be adapted to the different clinical and cultural contexts [49].…”
Section: Discussionmentioning
confidence: 99%